Climate seasonality and tree growth strategies in a tropical dry forest. (23rd January 2020) - García‐Cervigón, Ana I.; Camarero, J. Julio; Cueva, Eduardo; Espinosa, Carlos I.; Escudero, Adrián
Abstract: Questions: Do tree species in seasonally dry tropical forests differ in the timing of their secondary growth? And in their growth rates between consecutive years? If so, how are these contrasting patterns linked to seasonality in climatic variables (temperature, precipitation)? Which is the role of leaf phenology and functional traits as drivers of stem radial increment responses to climate? Location: A Tumbesian tropical dry forest in southern Ecuador. Methods: We used a 12‐year database of stem radial increments to characterize intra‐ and inter‐annual patterns of secondary growth in 13 co‐existing dominant tree species. For each species, we adjusted an additive model to describe intra‐annual increment patterns and created a mean series of annual increments to describe inter‐annual changes. Adjusted increments were then correlated with monthly temperature and rainfall data over the study period, and also with the crown percentage covered by leaves. The role of functional traits (leaf area, wood density, maximum tree height, seed dry mass) was explored using average trait values per species. Results: We observed continuous variation in the seasonality of radial increments, ranging from species that started incrementing their diameter as early as first rains occurred in the season to species that showed delayed responses. Variability in intra‐ and inter‐annual increment patterns was explained by functional traits (leaf area and seed dry mass, and maximum height and wood density, respectively) and leaf phenology, but this variation was not clearly matched with any functional trait configuration. This, combined with the absence of homogeneous responses of annual growth rates to climate, suggests the existence of contrasting strategies that virtually vary in a species‐specific fashion. Conclusions: Co‐existing tree species in seasonally dry tropical forests show different growth strategies to face intra‐ and inter‐annual climate variations, which may increase the resilience of these forests against projected climatic variations. Abstract : Tree growth in tropical dry forests is strongly determined by climatic seasonality. Co‐existing tree species show distinct strategies of seasonal growth to face water shortage, ranging from immediate to delayed responses to the first rains. Species‐specific growth strategies, coordinated with leaf phenology and mediated by different functional trait configurations, may increase the resilience of these forests against projected climatic variations.